The Influence of Endorser Promotion and Brand Attachment on Repurchase Intention with Mediation Brand Commitment - Faruqi, Faris; Larasati, Melyan Eka; Nursanita, Nursanita; Anthonino, Dean Salomo (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
The study delves into the influence of exogenous variables, specifically endorser promotions (X1) and brand attachment (X2), on the endogenous variable, repurchase intention (Y), mediated by brand commitment (Z). Conducted via quantitative methods and SmartPLS software, it targets Barenbliss consumers exposed to TikTok promotions. Primary data was collected through Google Forms and Excel. Findings reveal direct effects: (1) Endorser promotions positively impact repurchase intention, (2) Brand attachment lacks a direct effect on repurchase intention, (3) Endorser promotions positively affect brand commitment, while (4) Brand attachment does not directly impact brand commitment. Additionally, (5) Brand commitment positively influences repurchase intention. Indirect effects include: (6) Endorser promotions impacting repurchase intention through brand commitment, and (7) No indirect effect of brand attachment on repurchase intention via brand commitment. The study underscores the importance of bolstering endorser promotions on TikTok to enhance repurchase intentions. Strengthening brand commitment through high-quality collaborations fosters sustained repurchase intentions. While brand attachment's direct impact may be lacking, nurturing emotional connections with consumers remains vital. Integrating effective endorser promotions with strategies to cultivate brand attachment nurtures loyalty and fosters enduring consumer relationships.